1990
DOI: 10.1177/001872089003200207
|View full text |Cite
|
Sign up to set email alerts
|

Work Preferences as Moderators of the Effects of Paced and Unpaced Work on Mood and Cognitive Performance: A Laboratory Simulation of Mechanized Letter Sorting

Abstract: This article describes a laboratory study of work preferences (ideal job demand and discretion levels) as moderators of the effects of paced and unpaced work on cognitive and affective responses. Posttest measures of cognitive performance and self-reported stress and arousal were used as outcome measures with covariance control for the corresponding pretest values. The experimental design allowed within-subjects contrasts of fast versus slow pacing and of machine-paced versus self-paced conditions. Self-paced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…In addition, high-demand conditions were characterised by higher perceived task stressfulness and lower task satisfaction relative to low-demand conditions. Finally, consistent with previous experimental studies (e.g., Bohlin et al, 1986;Hockey and Earle, 2006;Hutt and Weidner, 1993;Parkes et al, 1990;Rau, 1996), high-demand exerted deleterious effects on mood. Specifically, high-demand was associated with significantly higher post-task levels of negative mood and stress, and lower post-task levels of positive mood and arousal relative to low-demand.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, high-demand conditions were characterised by higher perceived task stressfulness and lower task satisfaction relative to low-demand conditions. Finally, consistent with previous experimental studies (e.g., Bohlin et al, 1986;Hockey and Earle, 2006;Hutt and Weidner, 1993;Parkes et al, 1990;Rau, 1996), high-demand exerted deleterious effects on mood. Specifically, high-demand was associated with significantly higher post-task levels of negative mood and stress, and lower post-task levels of positive mood and arousal relative to low-demand.…”
Section: Discussionsupporting
confidence: 90%
“…The vast majority of prior experimental research investigating the D-CM has mainly used between-participants designs (see Flynn & James, 2009; Häusser, Mojzisch, & Schulz-Hardt, 2011; Jimmieson & Terry, 1997, 1998, 1999; O'Brien, Terry, & Jimmieson, 2008; Parker et al, 2009; Perrewe & Ganster, 1989; Searle, Bright, & Bochner, 1999, 2001 ). Only three experimental studies investigate task demands, such as workload, using methods that take into account within-participant effects (Glaser, Tatum, Nebeker, Sorenson, & Aiello, 1999; Hockey & Earle, 2006; Parkes, Styles, & Broadbent, 1990). Based on recent evidence from experience sampling studies indicating that task demands fluctuate on a day-to-day basis at work (Butler, Grzywacz, Bass, & Linney, 2005; Daniels, Boocock, Hartly, & Holland, 2009; Daniels & Harris, 2005), it is now crucial to incorporate a temporal dimension into studies on work demands and control.…”
Section: Within-participants Approach: Adaptation and Reactivity To W...mentioning
confidence: 99%
“…With regard to performance outcomes, Parkes, Styles, & Broadbent (1990) found that speed and accuracy on a mail-sorting task suffered in cases of mismatch. However, the mail-sorting task did not test the complex thinking and decision-making necessary in many organizational settings.…”
Section: Match and Mismatch Between Desire For Control And Work Controlmentioning
confidence: 99%